2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28652
|View full text |Cite
|
Sign up to set email alerts
|

Matched Assessment Data Set for Experiment-Centric Pedagogy Implementation in 13 HBCU ECE Programs

Abstract: is a professor in the Department of Electrical, Computer, and Systems Engineering (ECSE) where he teaches courses on electromagnetics, electronics and instrumentation, plasma physics, electric power, and general engineering. His research involves plasma physics, electromagnetics, photonics, biomedical sensors, engineering education, diversity in the engineering workforce, and technology enhanced learning. He learned problem solving from his father (ran a gray iron foundry), his mother (a nurse) and grandparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…They played critical roles in the design, implementation and verification of both the Mobile Studio and Analog Discovery by providing a variety of engineering design support, component selection, prototype verification, manufacturing and test assistance. This paper addresses whether the M1K can be utilized in undergraduate courses based on evaluation by instructors participating in the HBCU Experiment Centric Pedagogy (ECP) project [1,2]. In this project, faculty from the 13 HBCUs with ECE programs have been implementing ECP in their first year, circuits, electronics and design courses for the last three years using Analog Discovery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They played critical roles in the design, implementation and verification of both the Mobile Studio and Analog Discovery by providing a variety of engineering design support, component selection, prototype verification, manufacturing and test assistance. This paper addresses whether the M1K can be utilized in undergraduate courses based on evaluation by instructors participating in the HBCU Experiment Centric Pedagogy (ECP) project [1,2]. In this project, faculty from the 13 HBCUs with ECE programs have been implementing ECP in their first year, circuits, electronics and design courses for the last three years using Analog Discovery.…”
Section: Methodsmentioning
confidence: 99%
“…Essentially all of these papers report learning gains through the use of these powerful and generally inexpensive platforms. A sampling of the best of these papers is found in the references [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]21]. One of the most elegant studies has been reported in a series of papers by Ferri et al [7] from Georgia Tech where they added hands-on modules using myDAQs in a variety of courses that previously had no experimental component.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment Under Special Circumstances is a smaller category, but addresses the particular problems encountered, and lessons learned, by special types of universities such as HBCUs [12] and liberal arts universities [11], and in programs doing assessment in multiple locations [13] or across multiple programs [10]. Also in this category are programs involving cooperative education [14] and industrial internships [15] in their assessment processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hands-on activities were shown to be successful across a variety of instructional settings and introductory EE topics. [1,2,3,4,5]…”
Section: Introductionmentioning
confidence: 99%